PRODUCTION OF TOURISTIC TERRITORY IN THE REGION OF AGRARIAN CONFLICT: THE CASE OF ROSANA-SP - Santos, Clediane Nascimento [UNESP]; Cortez Thomaz, Rosangela Custodio [UNESP] (Univ Federal Ceara, Programa Pos-graduacao & Filosofia, 2015)
This study aimed to analyze the production of territory by tourism, especially the rural settlements of Rosana - SP municipality. For this case study was used the literature search and semi-structured interviews with a script prepared in advance, as this flexibility allows the insert issues that arising in the course of the interview by the researcher. The subjects are the organizers of cultural events that shape the cultural territoriality, such as wheel viola, revelry of kings and managers related to the attractions already formatted, such as the Regional Museum of Memory, the power plant, as well as municipal management for tourism. With the analysis of the granted interviews and observation it was found that tourism could contribute to the enhancement of cultural and heritage territoriality.
Keywords: Rural Tourism; Rural Settlements; Rosana